(untitled) (REMUNOM, 2024)
The aim of this study was to assess the importance of the role of dental surgeons in the early diagnosis of immunologically mediated and autoimmune diseases with repercussions in the oral cavity. This is a narrative literature review with a documentary and observational approach. The databases used to search the literature were PubMED, SCIELO, LILACS and Google Scholar. The keywords used were "autoimmune diseases", "dental care", "oral manifestations" and "diagnosis". This method of navigation ensured that all the words containing these fragments were identified, making it easier to select and choose the publications that met the study’s inclusion criteria for subsequent analysis. This research included full articles, literature reviews and epidemiological studies. Course completion papers, dissertations, abstracts or theses were not included. The identification of immunologically mediated and autoimmune diseases at an early stage demonstrates the importance of dental surgeons treating them beforehand, as well as minimizing the progression and symptoms of certain diseases through drug intervention and thus avoiding the development of opportunistic pathologies. Dental surgeons therefore need to be fully aware of the clinical signs and symptoms that autoimmune diseases can present in the oral cavity, in order to be able to carry out an early diagnosis and correct multidisciplinary treatment of patients with these conditions.